Ecoenzymes as Biocatalysts: Accelerating Biofilm Formation in Wastewater Biofilters - Pitriani Pitriani; Kiki Sanjaya; Alchamdani Alchamdani; Ade Sofyan Anas; Riri Suwahyuni Wahid; Sendhy Krisna Sari (Media Publikasi Cendekia Indonesia, 2026)
Biofilters have advantages in waste treatment, but limitations related to the formation time of biofilms, which play an important role in reducing pollutants in wastewater. The addition of biocatalysts such as ecoenzymes can be an innovative solution in accelerating biofilm formation. This study aimed to examine the effectiveness of adding ecoenzyme to biofilter in accelerating biofilm formation. This research is quantitative with an experimental approach using a completely randomized design (CRD), The test was conducted by adding 10% orange peel ecoenzyme, where the characteristic test shows that this ecoenzyme is better quality than those made from vegetable waste. Data collection was carried out through: (1) Field observation, (2) In-situ measurement, and (3) Microscopic observation. The data was analyzed descriptively to examine the quality of ecoenzymes, meanwhile, biofilm development was observed microscopically. The result found the ecoenzyme has a distinctive fermented aroma, is dark brown colour, pH < 4 and normal temperature, this indicates that the ecoenzyme is of good quality. Identification of lactic acid bacteria (LAB) revealed 53 colonies with large and small round morphology and a cloudy white colour. Lactobacillus bacteria dominated, both Gram-positive and Gram-negative found, rod-shaped, and large round colonies. Based on microscopic observation, biofilm formation in the control group was slower than in the samples treated with 10% ecoenzyme, a biofilm formation began to appear on the first day. While in the control samples it only appeared on the third day. This indicates that the ecoenzyme addition may accelerate biofilm formation.